Association between postpartum depression and breastfeeding self-efficacy in mothers: a systematic review and meta-analysis - Golnaz Sadat Ahmadinezhad; Fatemeh Zahra Karimi; Mahboobeh Abdollahi; Elham NaviPour (BMC Pregnancy and Childbirth, 2024)
Abstract Background Depression is one of the most common mental disorders in the postpartum period. Depression can decrease self-efficacy in breastfeeding by reducing the mother’s self-confidence. Considering the conflicting results regarding the relationship between postpartum depression and breastfeeding self-efficacy, this systematic review was conducted to investigate the relationship between breastfeeding self-efficacy and postpartum depression. Method In this systematic review, published articles in PubMed, Scopus, Web of Sciences, Cochrane Library, and Google Scholar databases were searched using English keywords “Self-efficacy, breastfeeding, breastfeeding Self-efficacy, depression, postpartum depression” without publication date limit. Data analysis was done with employing STATA14 software. Heterogeneity was assessed using I2 index which was 0%. Therefore, the fixed effects method was used to combine the data and perform meta-analysis. Result The results of the meta-analysis showed that based on the fixed effect method, depression was associated with decreased breastfeeding self-efficacy on the first day (SMD = 0.62, 95%CI: -0.830, -0.41, p = 0.0001) and on the third day (SMD = 0.84, 95% CI: -0.55,1.14, p = 0.0001). The Begg and Manzumdar test revealed no publication bias, with p = 0.317. Conclusion Postpartum depression may be associated with a decrease in the mother’s breastfeeding self-efficacy and placing mother in a condition to pay low attention to her maternal role. Therefore, healthcare providers should provide adequate support according to the needs of mothers and develop diagnostic and treatment protocols to improve the level of maternal health.